The Value of a Comprehensive Genomic Evaluation in Prenatal Diagnosis of Genetic Diseases: A Retrospective Study - Fu, Fang; Li, Ru; Yu, Qiu-Xia; Dang, Xiao; Yan, Shu-Juan; Zhou, Hang; Cheng, Ken; Huang, Rui-Bin; Wang, You; Zhang, Yong-Ling; Jing, Xiang-Yi; Zhang, Li-Na; et al. (Genes, 2022)
Currently, there are still many challenges in prenatal diagnosis, such as limited or uncertain fetal phenotyping, variant interpretation, and rapid turnaround times. The aim of this study was to illustrate the value of a comprehensive genomic evaluation in prenatal diagnosis. We retrospectively reviewed 20 fetuses with clinically significant copy number variants (CNVs) detected by chromosomal microarray analysis (CMA) and no further exome sequencing testing in our tertiary center between 2019 and 2020. The residual DNA from the prenatal cases was used for the parallel implementation of CNV sequencing (CNV-seq) and trio-based clinical exome sequencing (trio-CES). CMA revealed 26 clinically significant CNVs (18 deletions and eight duplications) in 20 fetuses, in which five fetuses had two or more CNVs. There were eight fetuses with pathogenic CNVs (e.g., del 1p36), nine fetuses with likely pathogenic CNVs (e.g., dup 22q11.21), and three fetuses with variants of unknown significance (VOUS, e.g., dup 1q21.1q21.2). Trio-CES identified four fetuses with likely pathogenic mutations (SNV/InDels). Of note, a fetus was detected with a maternally inherited hemizygous variant in the SLX4 gene due to a 16p13.3 deletion on the paternal chromosome. The sizes of CNVs detected by CNV-seq were slightly larger than that of the SNP array, and four cases with mosaic CNVs were all identified by CNV-seq. In conclusion, microdeletion/duplication syndromes and monogenic disorders may co-exist in a subject, and CNV deletion may contribute to uncovering additional recessive disease alleles. The application of a comprehensive genomic evaluation (CNVs and SNV/InDels) has great value in the prenatal diagnosis arena. CNV-seq based on NGS technology is a reliable and a cost-effective technique for identifying CNVs.